Publications Received (Academy of Management Review, 1990)
A list of management publications received by the journal is presented. They include “Moral Management: Business Ethics,” by Andrew F. Sikula, “New-Product Development and Testing,” by Walter Henry, Michael Menasco, and Hirokazu Takada, and “The Regulation of Monopoly,” by Roger Sherman.